CONNECTING TEACHER’S ACTIVITY AND STUDENTS’ ACHIEVEMENT TOWARD NUMERACY COMPETENCY IN LEARNING MATHEMATICS - Nasrullah Pemu (Pedagogy: Jurnal Pendidikan Matematika, 2023)
This research aims to connect the construction of teacher activities and student learning outcomes that support the numeracy competence of learners in mathematical learning activities. To support the achievement of this goal, classroom action research is an applied method. This research activity was carried out at SMPN 33 Makassar by involving not only teachers as many as 2 people, students 2 people, and students as many as 28 people as learning subjects. The research instruments used include tests, observation sheets, student worksheets, textbooks, and learning media. The results showed that the numeracy competence of SMPN 33 Makassar learners still requires special intervention, learning activities implemented by teachers have not been effective in helping students achieve the expected level of numeracy competence, students need learning activities that encourage them to understand phenomena and associate them with mathematical concepts, as well as solving problems involving numeracy ability.